Search for one large extra dimension with the DELPHI detector at LEP - Abdallah, J; Abreu, P; Adam, W; Adzic, P; Albrecht, T; Alemany-Fernandez, R; Allmendinger, T; Allport, P; Amaldi, U; Amapane, N; Amato, S; Anashkin, E; et al. (Springer Science and Business Media, LLC, 2009)
Single photons detected by the DELPHI experiment at LEP2 in the years 1997-2000 are reanalysed to investigate the existence of a single extra dimension in a modified ADD scenario with slightly warped large extra dimensions. The data collected at centre-of-mass energies between 180 and 209 GeV for an integrated luminosity of ~650 pb-1 agree with the predictions of the Standard Model and allow a limit to be set on graviton emission in one large extra dimension. The limit obtained on the fundamental mass scale MD is 1.69 TeV/c2 at 95% CL, with an expected limit of 1.71 TeV/c2 . © 2009 Springer-Verlag / Società Italiana di Fisica.